A Well-Knit Agro Supply Chain As A Precursor To Growth And Development Of Horticulture (International Journal of Scientific Research and Management (IJSRM), 2015)
India loses a huge amount of horticulture produce every year specially fruits and vegetables. More 25%= (Srivastava and Kumar, 2010) horticulture produce goes to natural dustbin which is world’s highest spoilage rate. India lacks cold storage, effective food packaging as well as safe and efficient rural transportation system. On agricultural research and development (R&D), India spends only 1% of agricultural GDP, thereby ranking amongst the bottom of 26 lower middle-income countries in the index (Sukhmeet, 2013). India is also facing inadequate and inefficient rural credit supply. This phenomenon poses great challenges before the implementation of National Food Security Act, rural economy and growth and development of horticulture.